Comprehensive review of spiral heat exchanger for diverse applications. (2023) - Irabatti, Vedant; Patil, Yash; Kore, Sandeep; Barangule, Vaishnavi; Kothe, Abhishek
Abstract: Energy-saving is a very important issue in our world and heat exchanger is very useful for saving energy. Heat exchanger selection is very important in process industries like dissolution, fermentation, crystallization, etc. Spiral Heat Exchangers (SHE) are known for their compact design and excellent heat transfer efficiency when compared to their conventional counterparts. The surface area utilized for heat transfer is much larger in a spiral heat exchanger as compared to conventional designs like shell-type heat exchangers for the same volume occupied. These advantages make SHEs much more suitable for a variety of applications in processing industries. This present article focuses on the research and optimization done by various researchers across the world to improve the efficiency of spiral heat exchangers by different approaches.